Antibacterial properties and mechanisms of toxicity of sonochemically grown ZnO nanorods. Issue 4 (8th December 2014) - Okyay, Tugba O.; Bala, Rukayya K.; Nguyen, Hang N.; Atalay, Ramazan; Bayam, Yavuz; Rodrigues, Debora F.
Abstract : ZnO nanorods produced sonochemically prevented microbial growth, biofilm formation and were non-toxic to mammalian cells. Abstract : In this study, we present a simple, fast and cost-effective sonochemical growth method for the synthesis of zinc oxide (ZnO) nanorods. ZnO nanorods were grown on glass substrates at room temperature without the addition of surfactants. The successful coating of substrates with ZnO nanorods was demonstrated by Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), and energy dispersive X-ray spectroscopy (EDS). The antimicrobial properties of ZnO nanorods against the planktonic Bacillus subtilis and Escherichia coli and their respective biofilms were investigated. The cytotoxicity of ZnO nanorods were evaluated using the NIH 3T3 mammalian fibroblast cell line. Moreover, to understand the possible mechanisms of ZnO nanorod toxicity, glutathione oxidation, superoxide production, and release of Zn 2+ ions by the ZnO nanorods were determined, and the LIVE/DEAD assay was employed to investigate cell membrane damage. The results showed that sonochemically grown ZnO nanorods exhibited significant antimicrobial effects to both bacteria and prevented biofilm formation. ZnO nanorods did not present any significant toxicity to fibroblast cells. The main anti-microbial mechanisms of ZnO nanorods were determined to be H2 O2 production and cell membrane disruption.